Vault finals analysis in women's artistic gymnastics at world competitions 2016-2019 - Corlaci, I.; Gavojdea, A. M.; Manos, M.; Ferreirinha, J. (Physical Education, Sport and Kinetotherapy Journal, 2020)
Women`s Artistic Gymnastics manages to raise a great deal of interest from both spectators and TV viewers. Though the Vault event has a short execution time, it is a highly dynamic and spectacular performance that makes it very attractive to the public. The preparation for those 5-7 seconds of performance on the vault apparatus must be very rigorous. Athletes need to be complete in terms of mastering their motor skills, showing courage, good spatial-temporal orientation and elegance. The final score depends on all of these elements. The reason for choosing the theme of this paper is to conduct an assessment of qualified athletes by nation and identify the vaults performed at world competitions in the vault apparatus finals between 2016 and 2019. The purpose is to identify and monitor for analysis the most complete athletes performing vaults during the apparatus finals. In addition, we would like to see whether there are any particular vaults or groups of vaults favoured by athletes in order to increase their advantage over other competitors. For this analysis, we used as research methods: bibliographic study, observation, monitoring and statistical analysis of the data collected from the processing and interpretation of the results achieved by our sample. Following the analysis conducted on the subjects of this research during the four years of study, we can conclude that the most complete athletes have at least two vaults of high technical value and increased difficulty in their sports portfolios.